2019
DOI: 10.1109/access.2019.2947772
|View full text |Cite
|
Sign up to set email alerts
|

Design of New Circularly Polarized Wearable Dielectric Resonator Antenna for Off-Body Communication in WBAN Applications

Abstract: A unique circularly polarized (CP) compact wearable dielectric resonator antenna (DRA) has been proposed for off-body communication in wireless body area network (WBAN) applications. The design is singly fed and a new H-shaped conformal metal strip has been used to excite the DRA. A circular polarization over a bandwidth of ∼9.6% (7.47-8.25 GHz) in conjunction with an impedance matching bandwidth of ∼20.7% (6.95-8.68 GHz) has been offered by the antenna. A prototype has been fabricated and measured. The antenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Although the CP DP antenna in Reference 25 has a wider AR bandwidth, the low‐profile characteristic cannot be kept. On the other hand, benefiting from the adoption of the DP antenna, it can be observed that the proposed antenna owns a lower profile and a higher gain than all CP DR antennas in References 12‐17 The gain of CP DR antenna in Reference 16 is higher than that of the proposed antenna, partly because a relatively large reflector is used.…”
Section: Experiments Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the CP DP antenna in Reference 25 has a wider AR bandwidth, the low‐profile characteristic cannot be kept. On the other hand, benefiting from the adoption of the DP antenna, it can be observed that the proposed antenna owns a lower profile and a higher gain than all CP DR antennas in References 12‐17 The gain of CP DR antenna in Reference 16 is higher than that of the proposed antenna, partly because a relatively large reflector is used.…”
Section: Experiments Resultsmentioning
confidence: 92%
“…To achieve higher data rate and larger information capacity, many approaches have been reported to expand the 3 dB axial ratio (AR) bandwidth of the CP DR antenna, 12‐19 which can be mainly classified into two categories. In the first approach, the multiple modes are merged together by employing special‐shaped DR such as hollow cylindrical, 12 spidron fractal, 13 high‐aspect ratio, 14 stair‐shaped, 15 and two‐layer nested 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This section highlights the state‐of‐the‐art developments of CPDRA using single point feed 11‐64 and multi‐point feed power divider, 65‐76 along with modification of three dimensional DR shapes 77‐103 . In this review article, the authors have segregated CP mechanism in terms of excitation of feeding techniques like microstrip line, coaxial probe, and aperture coupled feed, which will be helpful to the researcher to get the complete idea about the developments of particular excitation feeding method …”
Section: Techniques To Generate Cpdramentioning
confidence: 99%
“…One of the fundamental subjects in the broad area of DRA is the excitation scheme, which deals with the problem of how to couple the electromagnetic energy from the feeding transmission line to the dielectric radiator efficiently. Feeding techniques can be divided into single point feed and multi‐point feed power divider, which plays an important role in generation of CP for the case of DRA over three and half decades 11 ‐76 …”
Section: Techniques To Generate Cpdramentioning
confidence: 99%